Databases fit for blockchain technology: A complete overview - Kalajdjieski, Jovan; Raikwar, Mayank; Arsov, Nino; Velinov, Goran; Gligoroski, Danilo (Elsevier, 2023)
Efficient data storage and query processing systems play a vital role in many different research areas. Blockchain technology and distributed ledgers attract massive attention and trigger multiple projects in various industries. Nevertheless, blockchain still lacks the features of a Database Management System (DBMS or simply databases), such as high throughput, low latency, and high capacity. For that purpose, there have been many proposed approaches for handling data storage and query processing solutions in the blockchain. This paper presents a complete overview of many different DBMS types and how these systems can be used to implement, enhance, and further improve blockchain technology. More concretely, we give an overview of 10 transactional, an extensive overview of 14 analytical, 9 hybrids, i.e., translytical, and 13 blockchain DBMSs. We explain how database technology has influenced the development of blockchain technology by unlocking different features, such as Atomicity, Consistency, Isolation, and Durability (ACID), transaction consistency, rich queries, real-time analysis, and low latency. Using a relaxation approach analogous to the one used to prove the Consistency, Availability, Partition tolerance (CAP)-theorem, we postulate a “Decentralization, Consistency, and Scalability (DCS)-satisfiability conjecture” and give concrete strategies for achieving the relaxed DCS conditions. We also provide an overview of the different DBMSs, emphasizing their architecture, storage manager, query processing, and implementation.
Keywords: BlockchainDatabasesTransactionsACIDAnalyticsTranslytical